ANALISIS PENGELOLAAN LOGISTIK PEMILU 2024 KPU PROVINSI JAWA TIMUR - Ningrum, Deva Mariana Isti; Tukiman, Tukiman (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Indonesia is a democratic country that uses an electoral system for every change of president. High quality general elections are very important to realize people's sovereignty in a democratic state government based on Pancasila and the 1945 Constitution of the Republic of Indonesia. To hold democratic elections, professional election organizers are needed who have integrity, capacity and accountability. The General Election Commission is an example. In this research, the author uses a descriptive approach as a qualitative research method. Qualitative research is a type of research that describes and analyzes events, phenomena, social activities, attitudes, beliefs, perceptions and thoughts of individuals and groups. Data was collected from interviews with three informants from the General Election Commission, which is responsible for logistics management for the 2024 election. As shown by the distribution of logistics for the 2024 election, the results show that the East Java Province General Election Commission manages state property well, including logistics election. However, several improvements and strengthening are needed in the human resources sector as well as warehouse and other logistics infrastructure so that the upcoming General Election can take place optimally and according to planning. Our common goal is successful simultaneous elections in 2024 with transparent financial administration and accountability. Keywords: Management; Elections; KPU